Triggered and maintained engagement with learning among gifted children in primary education - Snikkers-Mommer, Saskia; Hoekman, Johan; Mayo, Aziza; Minnaert, Alexander (Frontiers in Education, 2024)
Motivating gifted children to become and stay engaged with classroom tasks can be a huge struggle for primary education teachers. This concurrent parallel mixed method design study investigates the relative differences in importance of the basic psychological needs between gifted children and children with an average IQ with respect to triggered and maintained engagement to learn. 1,017 students (512 girls, 505 boys) stemming from 35 schools participated in this study. The qualitative analysis showed that children identify a wide array of theme's related to both the context of their learning experiences as well as to themselves. Besides, statistical analyses showed that while all children benefit from fulfilment of their basic psychological needs, gifted children experience a greater need for autonomy support to become engaged in school tasks. To maintain engaged, even in the face of resistance, all children regardless of their IQ indicate that structure is important. Possible implications for teachers are addressed in the discussion.